2011
DOI: 10.1016/j.rpor.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy-corresponding method of IMRT verification

Abstract: It seems, that the complex monitoring of treatment would be possible owing to the images obtained as a cross-examination of γ-images and corresponding DRRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…found out that IMRT dose planed provide more uniform coverage of the PTV than 3D-CRT and IMRT resulted in a significant reduction of mean and/or maximum doses to OAR; of particular note, these authors reported that the mean dose to the parotid glands decreased by a mean of 13.5 Gy with the use of IMRT vs. 3D-CRT 29. The revealed differences in dose parameters between evaluated techniques were small due to the improvement in optimization applied in all radiotherapy techniques, thus detection tools and methods that allowed to trace the differences had to be appropriately accurate 12,30,31…”
Section: Discussionmentioning
confidence: 99%
“…found out that IMRT dose planed provide more uniform coverage of the PTV than 3D-CRT and IMRT resulted in a significant reduction of mean and/or maximum doses to OAR; of particular note, these authors reported that the mean dose to the parotid glands decreased by a mean of 13.5 Gy with the use of IMRT vs. 3D-CRT 29. The revealed differences in dose parameters between evaluated techniques were small due to the improvement in optimization applied in all radiotherapy techniques, thus detection tools and methods that allowed to trace the differences had to be appropriately accurate 12,30,31…”
Section: Discussionmentioning
confidence: 99%
“…Hyperfractionation of RT dose and modern RT techniques with increased dose conformity ( e.g . intensity-modulated RT with image guidance) can further reduce the risk of optic neuropathy 23,24. Because only two cases with neck metastases of benign-appearing IPs have been reported so far7,25, no elective irradiation of regional lymphatics is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy corresponding method. This method was proposed to link gamma information to patient anatomy [30]. To overcome the absence of regional information in simple gamma analysis, the authors suggested a method that cross-examines gamma results on patient's digital reconstructed radiographs (DRRs).…”
Section: Biological-anatomy Related Methodsmentioning
confidence: 99%